Developmental compartments and planar polarity in Drosophila. - Casal, J.; Struhl, G.; Lawrence, P.A. (Current Biology, 2002)
Planar polarity refers to the asymmetry of a cell within the plane of the epithelium; for example, cells may form hairs that point in a posterior direction, or cilia may beat in one way. This property implies that cells have information about their orientation; we wish to understand the nature of this information. Relevant also is the body plan of insects, which, in the ectoderm and somatic mesoderm, consists of a chain of alternating anterior and posterior compartments - basic units of development with independent cell lineage and subject to independent genetic control.Using the abdomen of adult Drosophila, we have taken genes required for normal polarity and either removed the gene or constitutively expressed it in small clones of cells and observed the effects on polarity. Hitherto, all such studies of polarity genes have not found any difference of behavior between the different compartments. We report here that the three genes, four-jointed, dachsous, and fat, cause opposite effects in anterior and posterior compartments. For example, in anterior compartments, clones ectopically expressing four-jointed reverse the polarity of cells in front of the clone, while, in posterior compartments, they reverse behind the clone. These three genes have been reported by others to be functionally linked.This discovery impacts on models of how cells read polarity. At the heart of one class of models is the hypothesis that cell polarity is determined by the vector of a morphogen gradient. Here, we present evidence that cell polarity in the abdomen depends on at least two protein gradients (Fj and Ds), each of which is reflected at compartment borders. Consequently, these gradients have opposing slopes in the two compartments. Because all polarized structures made by abdominal cells point posteriorly, we surmise that cells in each compartment are programmed to interpret these protein gradients with opposite signs, pointing up the gradient in one compartment and down the gradient in the other.